USING OF ESSENTIAL OILS EXTRACTED FROM SOME SPICES TO EXTEND THE SHELF LIFE OF SOFT WHITE CHEECE - S. Kh. Badawi (Mesopotamia Journal of Agriculture)
Essential oils of aniseed, nigella and clove were used to extend the shelf life of soft white cheese preservation at 0.05% of curd weight and to get rid of whey before salting . Having been preserved in 250 gm cans and kept for 1, 7, 14, 21, 28 days at 5 Co, cheese was analyzed regarding the ratio of total solid materials, fat and protein . Microbic content was studied by counting the total number of bacteria, coliform bacteria, lipolytic and proteolytic bacteria .Results showed no significant differences of spice on cheese chemical composition for all treatments whereas storing duration had a significant effect . Inhibiting effect of aniseed oil , nigella and clove on microflora especially the total number of bacteria, coliform bacteria, lipolytic and proteolytic bacteria during storage periods was incorporeal . It was shown that the aniseed inhibiting effect was higher than those of nigella and clove . It was also shown that there were incorporeal differences of storage periods on sensory evaluation of fresh white cheese concerning flavour and bitterness due to essential oils effect . Results showed the possibility of using essential oils as preservatives . The study managed successfully to increase the preservation duration of white soft cheese stored for 28 days whereas the control expired after 7 days . it is recommended to add aniseed oil , nigella or clove to prolong the shelf life of white soft cheese without affecting its chemical properties .